Between broadcast yourself and broadcast whatever: YouTube´s homepage as a synthesis of its business strategy - De-Aguilera-Moyano, Miguel; Castro-Higueras, Antonio; Pérez-Rufí, José-Patricio (Profesional de la información, 2019)
YouTube is a company representative of its original context, Web 2.0, that originally positioned itself as an open and collaborative platform to broadcast videos created by all kinds of users; their slogan was, and remains, Broadcast yourself. The acquisition of YouTube by Google introduced it in the search for profit in the framework of OTT (over the top) communication. The YouTube homepage reveals the successive business policies followed by the platform. In this work we analyze the evolution of the unlogged homepage of YouTube Spain between 2009 and 2018. We observe the gradual disappearance of the videos produced by private users and its replacement by those made by professional users (youtubers) and cultural industries. There is a remarkable parallelism between the implementation of business models and the greater or lesser recommendation of video from one kind of user or another.